Histopathological and Immunohistochemical Features of Small to Big Satellite Nevus Uncover the Nevogenesis of Large/Giant Congenital Melanocytic Nevus - Jieyu Gu; Boxuan Wei; Bowen Gao; Ran Duan; Lingling Sheng; Danning Zheng; Yongyang Bao; Feng Xie (Journal of Immunology Research)
The nevogenesis of large/giant congenital melanocytic nevus (lgCMN) is a complex biological process including several integral prenatal stages. Limited by ethical concerns, the debate of whether lgCMN develops from the epidermis to the dermis or in the opposite direction remains controversial. With the present study of the accompanying satellite nevi, we tend to support that lgCMN develops from epidermis to dermis. The satellite nevi were divided into 3 groups: big (diameter >10 mm), medium (>5 mm but ≤10 mm), and small (≤5 mm). Hematoxylin and eosin and immunohistochemical staining (SOX10, Ki67, and p16) were performed to compare the nevocyte infiltration depth as well as the positively stained rates among these satellite nevi. Compared to big satellite nevi, less deeply the nevocytes infiltrated the dermis, as well as more cells expressed SOX10 and Ki67 in the epidermis and fewer cells expressed p16 in the dermis of small satellite nevi. Additionally, two specimens were obtained from each of 4 patients who underwent serial resections of lgCMN at an average interval of 1.75 years to examine the histopathological changes. In the present study, satellite nevi of different sizes represent different stages of lgCMN from early to late, deepening our comprehension of the sequential stages of lgCMN nevogenesis. Initially, abnormal nevocytes seeded, proliferated, and spread along the epidermis. At rete ridges that protrude from the papillary dermis within the epidermis, some nevocytes formed nests and gradually penetrated into the dermis. Eventually, the nevocytes infiltrated the dermis and entered a homeostatic state. This study provides new evidence supporting the theory of epidermal-to-dermal nevogenesis in lgCMN.